Academic performance and graduation evaluation in a Program of Stomatology - Cutipa Luque, Mariana (2021)
Objective: To determine the relationship between academic performance and the exit evaluation in stomatology students. Material and Methods: The study was observational, descriptive, and cross-sectional. The population consisted of the registry of 45 graduates. The study variables were performance in the final evaluation of the degree (Professional Proficiency Exam) and academic performance in the final year. Results: The average Professional Proficiency Exam (PPE) was 11.82 (Min = 8; Max = 15.20) and the average academic performance was 15.87 (Min = 9.03; Max = 18.40), finding a correlation low positive (Spearman=0.205). The average of the academic performance in the subjects in the clinical area in adult patients 14.92; clinic in pediatric patients 15.76; in the hospital area 15.02; and in the areas of oral public health 17.80. The average of the Professional Proficiency Exam was: in the clinical area in adult patients 11.10; clinic in pediatric patients 13.83; hospital 10.31; social dentistry 12.02. A minimum to low positive correlation was found in the clinical and social area; in the hospital area the correlation was minimal negative. Conclusion: There is a trend for better scores on PPE and academic performance in female students compared to males. There is no relationship between the results of the PPE and the academic performance of the internship and subjects of the last year of the Stomatology Program of the Peruvian University Cayetano Heredia.